Anatomical terminology of the internal nose and paranasal sinuses: cross-cultural adaptation to Portuguese - Bezerra, Thiago Freire Pinto; Stamm, Aldo; Anselmo-Lima, Wilma Teresinha; Fornazieri, Marco Aurélio; Melo, Nelson D’Ávila; Balsalobre, Leonardo; Jotz, Geraldo Pereira; Leão, Henrique Zaquia; Nunes, André Alencar Araripe; Felippu, Alexandre; Cedin, Antonio Carlos; Pinheiro-Neto, Carlos D.; et al. (Elsevier, 2018)
Introduction: Functional endonasal endoscopic surgery is a frequent surgical procedure among otorhinolaryngologists. In 2014, the European Society of Rhinology published the “European Position Paper on the Anatomical Terminology of the Internal Nose and Paranasal Sinuses”, aiming to unify the terms in the English language. We do not yet have a unified terminology in the Portuguese language. Objective: Transcultural adaptation of the anatomical terms of the nose and paranasal cavities of the “European Anatomical Terminology of the Internal Nose and Paranasal Sinuses” to Portuguese. Methods: A group of rhinologists from diverse parts of Brazil, all experienced in endoscopic endonasal surgery, was invited to participate in the creation of this position paper on the anatomical terms of the nose and paranasal sinuses in the Portuguese language according to the methodology adapted from that previously described by Rudmik and Smith. Results: The results of this document were generated based on the agreement of the majority of the participants according to the most popular suggestions among the rhinologists. A cross-cultural adaptation of the sinonasal anatomical terminology was consolidated. We suggest the terms “inferior turbinate”, “nasal septum”, “(bone/cartilaginous) part of the nasal septum”, “(middle/inferior) nasal meatus”, “frontal sinus drainage pathway”, “frontal recess” and “uncinate process” be standardized. Conclusion: We have consolidated a Portuguese version of the European Anatomical Terminology of the Internal Nose and Paranasal Sinuses, which will help in the publication of technical announcements, scientific publications and the teaching of the internal anatomical terms of the nose and paranasal sinuses in Brazil.
Terminologia anatômica nasossinusal: adaptação transcultural para o português
Keywords: Anatomy; Consensus; Cross-cultural adaptation; Nose; Paranasal sinus